Evaluation of pharmacological treatments for Phytomonas spp. in oil palms in the San Martín region, Peru - Zegarra-Arteaga, Oliviño (2024)
Sudden wilt is a lethal disease that affects oil palms at any stage of their life, from one-year-old plants onwards. Once symptoms appear, the palm dies quickly, usually within 1 to 2 months. The objective was to evaluate whether the drugs metronidazole, nitazoxanide and clindamycin were capable of controlling the disease once symptoms appeared after inoculating the pathogen in healthy plants. Methodology, healthy 8-year-old palm plants were drilled at a height of 50 cm, then they were inoculated with juice from inflorescences, buds and roots of diseased plants, symptoms appearing after seven months, immediately upon appearance, applications of the drugs for one month, subsequently leaving them under observation for five months. The results were that only plants treated with nitazoxanide survived, with emissions from 506 roots, 10 clusters and 7 buds observed. It was concluded that the drug nitazoxanide managed to control the disease, reflected in the observation of new roots, clusters and buds.